Effects of Transformer Oil Properties and Contamination on Its Spectral Response - Abu Bakar, Norazhar; Abu-Siada, Ahmed; Islam, Syed; El-Naggar, M. (CMD 2014, 2014)
UV Spectrophotometry is a non-intrusive test that can be employed to determine power transformer’s integrity. Light transmitted through transformer oil sample containing various contaminations is decreased by that fraction being absorbed and is detected as a function of wavelength. This paper investigates the impact of various contaminations and oil properties such as water content, acidity, interfacial tension and average voltage breakdown on the spectral response of the transformer oil. In this regard, various transformer oil samples are collected from in-service transformers and the aforementioned parameters are measured. Same oil samples are scanned with UV-Vis spectroscopic and the spectral responses are obtained and analysed.